SOSIALISASI WAWASAN KESEHATAN DASAR OLEH TIM KKN INTERNASIONAL UNIVERSITAS MATARAM INDONESIA DAN FUKUSHIMA MEDICAL UNIVERSITY JEPANG DI WILAYAH SENGKOL, KECAMATAN PUJUT, LOMBOK TENGAH - Nurhidayati, Siti Zainiah; Maulana, Farreh Alan; Saraswati, Putu Bella Aprillia; Hikmaturrohmi; Handayani, Ervina; Ramadhan, Moch. Fitrah; Shinozuka, Miho; Ikunaga, Arisa; Tate, Kazuma; Miyake, Masao; Hazama, Akihiro; Prasedya, Eka Sunarwidhi (Jurnal Abdi Insani, 2024)
Basic health literacy is fundamental knowledge that is crucial to be known from an early age by children and the general public. Health education provided from an early age will encourage children to live healthy lives, ultimately growing into a generation that is healthy, intelligent, and cheerful. However, the lack of facilities and infrastructure in schools, especially elementary schools located in remote areas, results in a limited understanding of basic health knowledge among children. Sengkol village is a village in the Pujut district that lacks the facilities and infrastructure to support the improvement of children's knowledge regarding basic health literacy. Therefore, Universitas Mataram (UNRAM), in collaboration with Fukushima Medical University (FMU), has initiated a program related to the popularization of medical knowledge (POMk), which involves the dissemination of basic health literacy in a simple and engaging manner using interactive learning methods and appropriate teaching aids related to the topics discussed. This enables children to better understand the basic health topics presented. The dissemination activities took place over two days in elementary schools in the Sengkol area, Central Lombok, namely Eco School Nusantara as a learning venue for children and SDN 4 Sengkol as a formal school. The topics covered during the dissemination included Body Puzzle, Dangers of Tobacco, Personal Hygiene and Sanitation (PHBS), and Nutrition Balance.